Pengaruh pengetahuan pedagogi kandungan, efikasi kendiri guru, persepsi guru dan kepimpinan instruksional pengetua terhadap amalan pedagogi terbeza - Rosidah, Ramli (2022)
Differentiated instruction (PT) is a teaching framework that involves meeting the needs of every student in producing learning opportunities for all. However, based on previous studies, teachers did not practise PT and thus affecting students’ performance and potential. This study examined the influence of pedagogical content knowledge (PPK), self-efficacy (EFK), teacher’s perception (PERS) and principals' instructional leadership (KIP) towards teachers' practices of PT (APT). A convergent parallel mixed-methods approach was employed. Data was collected from 373 teachers through online survey, followed by interviews and content analysis of the daily lesson plan (RPH) from 14 teachers. The hypothesised influences was tested using structural equation modeling via AMOS version 23, while ATLAS.ti version 9 was employed to assist the thematic analysis of the interviews and the RPH. The findings of SEM indicated that PPK, EFK, PERS and KIP significantly explained 70% of teachers’ APT. Besides, there were significant mediation effects of KIP between PPK, EFK and PERS towards APT. Through the thematic analysis of teachers’ interviews supported by analysis of teachers’ RPH, four themes emerged showing that teachers implemented PT in the elements of learning processes and learning products. The findings also showed that teachers faced several difficulties in implementing PT so as to clarify the findings of quantitative data on the role of principals as mediator in the influence of PPK, EFK and PERS towards teachers’ APT. The study contributes to this area of research interest by highlighting teachers’ variables that influence APT through the theoretical perspectives of Iceberg model. Findings can be used as a basis for the improvement of teachers’ ability in PT and thus lead to the improvement of the practices of PT in the classroom and further improve student achievement to the optimum level.